Preference on Renewal Energy by Operators of Tourist Standard Hotels in Kathmandu, Nepal - Ghimire, Bhawani; Muneenam, Umaporn; Techato, Kuaanan (International Journal of Energy Economics and Policy, 2024)
Although renewable energy sources are viable alternatives, their uptake by hotel owners is still uneven and frequently constrained. Preference mostly depends on the availability and cost of the renewal energy. This articles aimed to study; firstly, the operator’s preference, renewal energy pattern, renewable energy of tourist standard hotels in Kathmandu, Nepal; secondly, to find the barriers in using renewable energy ; third, to find out the expectation in policy reformation from the government to increase the use of renewal energy in the hotels. Data collected from 30 hotels through a convenience sampling method showed that preference for renewal energy is 80% for Electricity and 2% only for solar energy. Hotel operators agreed that using renewal energy in the hotel will save their time and cost, and expected the concessional rate as well as subsidy from the government on renewal energy with expectaton of policy reforms. All hotel operators mentioned that renewal energy like hydropower electricity was easily available and there were less barriers in use of renewal energy being in Capital City. However, barriers depends on the affordability, availability, geographical location also.Result may differ in different location. Only 2% preference for solar energy is good future research questions.